Pastoralism and natural resource management: The case of the pastoral Borana in southern Ethiopia - Desta, S. (Ethiopian Society of Animal Production, 2000)
The pastoral areas of Ethiopia are one of the most drought-vulnerable with chronic food deficiencies between 1980-1 and 1999-2000 these areas suffered 3 major droughts. In all droughts the Borana pastoralists lost 35-67 percent of their livestock. The position of the southern Ethiopian rangelands that is referred to as the Borana plateau comprises about 95,000 square km overall. The human population in the region including the Borana, the Somali, the Gabra and other minorities is about 410 thousand. This paper looks into the climate, vegetation, water situation in this pastoral areas and discusses the pastoral society, herd management; livestock production and marketing, and resource management and property rights.